Analysis Activities International Coastal Clean-up in Pantai Amal Baru, Tarakan Indonesia - Gazali Salim; Agus Indarjo; Mufrida Zein; Asriadi; Ayu Tri Fatma; Rezkyana; Nasrul; Rusli; Suriyanti; Nabila; Achmad Daengs GS; Rukisah; Christine Dyta Nugraeni (Future Science, 2020)
Tarakan administratively is a city which has a fairly wide coastal area both land and sea which is categorized ecologically as an island that has a high level of natural resources. The magnitude of this potential has a significant impact on large-scale exploitation to meet economic needs by not referring to environmental sustainability in a sustainable manner such as the presence of waste due to fisheries or community life activities on the coast. The purpose of this research is to study the analysis of international coastal cleanup (ICC) in the Pantai Amal Baru of Tarakan city. The main research results in the activities of the ICC on the Amal Baru beach found 3 different types of waste, namely the type of waste from seaweed cultivation at 608 kg with a percentage of 58.29%; types of waste from residents around the New charity beach by 405 kg with a percentage of 38.83%; the type of waste from nature is 30 kg with a percentage of 2.88%.